Carboxyl/cholinesterases: a case study of the evolution of a successful multigene family. - Oakeshott, J.G.; Claudianos, C.; Russell, R.J.; Robin, G.C. (BioEssays, 1999)
The evolution of organismal diversity among the Metazoa is dependent on the proliferation of genes and diversification of functions in multigene families. Here we analyse these processes for one highly successful family, the carboxyl/cholinesterases. One key to the expansion of the functional niche of this group of enzymes is associated with versatile substrate binding and catalytic machinery. Qualitatively new functions can be obtained by substitution of one or a very few amino acids. This crudely adapted new functionality is then refined rapidly by a pulse of change elsewhere in the molecule; in one case about 13% amino acid divergence occurred in 5-10 million years. Furthermore, we postulate that the versatility of the substrate binding motifs underpins the recruitment of several family members to additional noncatalytic signal transduction functions.